Support amid uncertainty: Long COVID illness experiences and the role of online communities - David Russell; Naomi J. Spence; Jo-Ana D. Chase; Tatum Schwartz; Christa M. Tumminello; Erin Bouldin (Elsevier, 2022)
Long COVID is characterized by persistent and debilitating long-term symptoms from COVID-19. Many persons with Long COVID began gathering in online communities during the early phases of the pandemic to share their illness experiences. This qualitative interview study explored the subjective experiences of 20 persons with Long COVID recruited from five online communities. Their understandings of illness and associated implications for social relationships with family and friends, healthcare professionals, and online community members were explored. Three themes were identified from our analysis, including (1) complex and unpredictable illness experienced amid an evolving understanding of the pandemic; (2) frustration, dismissal, and gaslighting in healthcare interactions; and (3) validation and support from online communities. These findings highlight the significant uncertainty that persons with Long COVID navigated, the features of their often dismaying healthcare experiences, and the ways in which online communities aided them in understanding their illness.